Language Variations Used PUBG Mobile Player By Tamy E-Sport Community In Lubuk Basung - Raflis Raflis; Fitria Nugraheni (Fakultas Sastra Universitas Ekasakti, 2022)
Language variations are often encountered in daily communication, one of which is in the communication of the online game PUBG Mobile player community. The game programming language is English, so they have indirectly learned to understand the meaning of the language used by the online game. Based on these reasons, the researcher wants to explain the language variations used PUBG Mobile players by Tamy e-sport community in Lubuk Basung and also the factors that cause it. This research uses the theory of Chaer and Agustina about language variations that are caused not only by their narrative, but also by their social interactions. The researcher used qualitative methods. The purpose of this research is to explain the form of language variations used in player PUBG Mobile and their factors. The results of the research show that in the communication of PUBG Mobile players by the Tamy e-sport community there are language variations in the form of code-mixing, abbreviation, and Jakarta dialect. Code-mixing is the most commonly found in their communication. The factors that influence language variation in the communication of PUBG Mobile players in the Tamy e-sport community are environmental factors, habitual factors, and practicality factors in speaking